The usefulness of high-risk HPV hybrid capture in patients with squamous cell atypia in cervical cytological examination - Flora A. Adorno; Daniele Cristina F. Lousada; Karina M. P. A. Coelho; Paulo Henrique C. França (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Introduction: The cervical cytological examination and the investigation of high-risk human papillomavirus (HPV) deoxyribonucleic acid (DNA) are well-known valuable tools for screening of cervical lesions, since they allow the early diagnosis of cancer and its precursor lesions. Objective: This study aimed to evaluate the ability of high-risk HPV DNA detection by hybrid capture to predict intraepithelial lesions and cancer in patients with initial cervical cytological diagnosis of atypical squamous cells (ASC). Method: Retrospective analysis of histological or cervical cytological results after one-year follow-up from hybrid capture for high-risk HPV DNA research in patients with previous ASC diagnosis. Sensitivity, specificity and positive and negative predictive values of hybrid capture were calculated in relation to the identification of squamous intraepithelial lesions. Results: Among the 163 patients previously diagnosed with ASC and absence of high-risk HPV DNA, nine (5.5%) showed low-grade (LSIL) or high-grade squamous intraepithelial lesion (HSIL) during the follow-up. On the other hand, among the 110 patients presenting ASC and high-risk HPV DNA positivity, 43 (39%) showed cervical lesions within one year. Sensitivity and specificity values and positive and negative predictive values applied to hybrid capture for the identification of squamous intraepithelial lesions were 82.3%, 69.3%, 38.1%, and 94.4%, respectively. Conclusion: Our results showed a high negative predictive value of hybrid capture for cervical lesions detection, in patients with previous diagnosis of ASC, when the high-risk HPV DNA research was negative.